Solutions to the New Threats to Academic Freedom? - Tooley, Michael (Bioethics, 2014)
In my commentary on Francesca Minerva's article ‘New Threats to Academic Freedom’, I agree with her contention that the existence of the Internet has given rise to new and very serious threats to academic freedom. I think that it is crucial that we confront those threats, and find ways to eliminate them, which I believe can be done. The threats in question involve both authors and editors. In the case of authors, I argue that the best solution is not anonymous publication, but publication using pseudonyms, and I describe how that would work. In the case of editors, my proposal is a website that a number of journals would have access to, where papers that editors judge to be clearly worthy of publication, but whose publication seems likely to set off a firestorm of public and media protest, could be published without any indication of the journal that had accepted the paper for publication.